2022
DOI: 10.1021/acsomega.2c01721
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Fluid-Assisted Fabrication of Pd Nanoparticles/Graphene Using a Choline Chloride–Oxalic Acid Deep Eutectic Solvent for Enhancing the Electrochemical Oxidation of Glycerol

Abstract: A green method for synthesizing Pd nanoparticles/graphene composites from a choline chloride–oxalic acid deep eutectic solvent (DES) without a reducing agent or a surfactant is reported. Deep eutectic solvents are usually composed of halide salts and hydrogen-bond donors, and many are biocompatible and biodegradable. The merits of deep eutectic solvents include that they serve as reducing agents and dispersants, and Pd nanoparticles are tightly anchored to graphene. The size and dispersion of Pd particles are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…This is simply an indication that the coating at the surface of the Fe 3 O 4 cores is thicker than 10 nm and fully covers the cores, so we were not able to observe peaks related to Fe 3 O 4 NPs. The high-resolution XPS curve of Pd 3p and Pd 3d showed the double peaks of Pd 3p with binding energies of 532.6 and 560.8 eV which could be attributed to the Cu(0) 3p3/2 and 3p1/2, respectively, and the double peaks of Pd 3d with binding energies of 335.8 and 340.9 eV were accredited to the Pd(0) 3d5/2 and 3d1/2, respectively, that confirmed the existence of metallic palladium and the absence of palladium oxide in the final catalyst (Figure b and c). Additionally, the N 1s high-resolution XPS spectrum demonstrated a separation into two distinct peaks, with values of 398.7 and 399.9 eV for Fe 3 O 4 @MON and 399.0 and 400.3 eV for catalyst-1, respectively (Figure d and e). , The chemical shifts observed indicate that there is chelation occurring between nitrogen present in the MON shell materials and the palladium nanoparticles. This finding is consistent with the analysis performed by using PiFM.…”
Section: Resultsmentioning
confidence: 82%
“…This is simply an indication that the coating at the surface of the Fe 3 O 4 cores is thicker than 10 nm and fully covers the cores, so we were not able to observe peaks related to Fe 3 O 4 NPs. The high-resolution XPS curve of Pd 3p and Pd 3d showed the double peaks of Pd 3p with binding energies of 532.6 and 560.8 eV which could be attributed to the Cu(0) 3p3/2 and 3p1/2, respectively, and the double peaks of Pd 3d with binding energies of 335.8 and 340.9 eV were accredited to the Pd(0) 3d5/2 and 3d1/2, respectively, that confirmed the existence of metallic palladium and the absence of palladium oxide in the final catalyst (Figure b and c). Additionally, the N 1s high-resolution XPS spectrum demonstrated a separation into two distinct peaks, with values of 398.7 and 399.9 eV for Fe 3 O 4 @MON and 399.0 and 400.3 eV for catalyst-1, respectively (Figure d and e). , The chemical shifts observed indicate that there is chelation occurring between nitrogen present in the MON shell materials and the palladium nanoparticles. This finding is consistent with the analysis performed by using PiFM.…”
Section: Resultsmentioning
confidence: 82%
“…For example, one-step synthesis of Pd nanoparticle/graphene composites can be achieved by using ChCl/OA-based DES as a reducing agent, dispersant, and solvent. [121] The obtained Pd-based product exhibits a negative oxidation onset potential (−0.33 V) and a high peak current (42.6 mA cm −2 ) for the GOR. To achieve highefficiency conversion of electric energy to chemical energy, more advantages of DESs should be utilized to develop more electrocatalysts with higher selectivity.…”
Section: Mormentioning
confidence: 94%
“…ChCl/urea-based DES (1:2 m) Pt/CNTs-80 [ 114] Solvent ChCl/urea-based DES (1:2 m) Pt 1 (CeO 2 ) 0.5 /MWCNTs-D [ 57] Solvent and template: stabilizer ChCl/urea-based DES (1:2 m) Flower-like NiO [ 118] Template: crystal structure directing agent Ionothermal method-H 2 O precipitation 90.2% retention of peak current density over 300 cycles ChCl/OA-based DES (1:2 m) sc-Pd NPs/GR/SPCE [121] Reducing agents and template: dispersant Ionothermal method + supercritical CO 2 treatment GOR Onset potential −0.33 V and 41.49 mV/decade in 1 m Gly + 1 m KOH ChCl/urea-based DES (1:2 m) Pd-FNNs [ 122] Solvent and template Pressurized ionothermal method FAOR Mass activity: 1551.8 mA mg Pd −1 in 1.0 m HCOOH + 0.5 m H 2 SO 4…”
Section: Mormentioning
confidence: 99%
“…Abbott et al reported these green solvents firstly have received intensive attention in electrocatalysis applications due to their remarkable physicochemical properties (high conductivity, thermostability, negligible vapor pressure and wide electrochemical potential windows) [ 35 ]. Recently, Hsieh et al prepared sc-Pd NPs/GR/SPCE (screen-printed carbon electrode) which shows excellent activity towards glycerol oxidation compared to composites not fabricated by sc CO 2 processes [ 36 ]. Palomar-Pardavé et al prepared Pd@Pd(OH) 2 core-shell nanoparticles in DES.…”
Section: Introductionmentioning
confidence: 99%